The important role of radiation treatment in the management of Merkel cell carcinoma. (31st October 2013) - Hruby, G.; Scolyer, R.A.; Thompson, J.F.
Abstract : What's already known about this topic? Most studies of Merkel cell carcinoma are retrospective, contain heterogeneous patient populations treated according to clinician preference, and often over an extended period. What does this study add? This review updates the existing literature, including analysis of the only randomized trial in this disease, as well as the sequential prospective trials performed by the Trans‐Tasman Radiation Oncology Group investigators. The review indicates the importance of integrating radiation treatment, with or without chemotherapy, with surgery in the multidisciplinary management of this rare disease. Summary: Merkel cell carcinoma is an aggressive, radiosensitive cutaneous neuroendocrine tumour. In this review, the roles of radiation therapy and chemoradiation in the management of Merkel cell carcinoma are described and discussed, and guidelines for patient management are presented. Radiation treatment may be indicated for definitive (> 55 Gy) or adjuvant (> 50 Gy) treatment of the primary tumour site and for prophylactic (> 50 Gy), adjuvant (> 50 Gy) or definitive (> 55 Gy) treatment of the regional lymph node field. If a patient presents with positive margins after initial biopsy or resection, definitive radiation therapy or chemoradiation may be an alternative to further surgery and, importantly, results in less delay than re‐resection followed by adjuvant radiation treatment. Given the rarity of this tumour, patients should be enrolled on prospective databases and clinical trials, and managed in a multidisciplinary clinical setting wherever possible.